What determines the duration of a fiscal consolidation program? - Agnello, Luca (2013)
This paper assesses the determinants of the length of fiscal consolidation using annual data for 17 industrial countries over the period 1978–2009. Relying on a narrative approach to identify fiscal consolidation episodes, we show that fiscal variables (such as the budget deficit and the level of public debt) and economic factors (such as the degree of openness, the inflation rate, the interest rate and per capita GDP) are crucial for the fiscal consolidation process. Additionally, we employ duration analysis over a set of consolidation spells and find that, as time goes by, the likelihood of a fiscal consolidation ending is higher. However, the hazard function is not monotonic: indeed, it increases until the eighth or ninth year and starts decreasing afterwards. We also find that: (i) spending-driven consolidations are shorter than tax-driven consolidations; (ii) both types of consolidation are longer in Non-European countries than for European countries; and (iii) the size of the consolidation program (in percentage of GDP) does not significantly affect duration. All in all, our results support the importance of cuts in government spending as a way of bringing economies into a sustainable path for public debt. Moreover, they highlight the role played by a fiscal framework that imposes discipline in governments as a device to credibly shorten the length of fiscal consolidation episodes.